Phytochemical and pharmacology effect of Panax notoginseng - Bui Thanh Tung, Nguyen Thanh Hai (Journal of Applied Pharmaceutical Science, 2016)
Panax notoginseng has been shown beneficial effects on the cardiovascular system and traditionally used to prevent cerebral ischemia. It has haemostatic, antioxidant, hypolipidaemic, hepatoprotective, renoprotective and estrogen-like activities. The phytochemical compositions of the Panax notoginseng are mainly saponins, which belong to protopanaxatriol and protopanaxadiol group. Furthermore, Panax notoginseng also has some compounds such as notoginsenoide, flavonoids, phytosteroid. The present review focuses on phytochemical and important pharmacology effect of Panax notoginseng including antioxidant, antiinflammation and antithrombotic activities.
Keywords: Panax notoginseng, antioxidant, antiinflammation, antithrombotic, phytochemical.